1988
DOI: 10.1093/oxfordjournals.aje.a114977
|View full text |Cite
|
Sign up to set email alerts
|

Social Connections and Mortality From All Causes and From Cardiovascular Disease: Prospective Evidence From Eastern Finland

Abstract: The association between an a priori measure of social connections and five-year mortality from all causes, cardiovascular diseases (International Classification of Diseases, Eighth Revision (ICD-8) codes 390-458), and ischemic heart disease (ICD-8 codes 410-414) was studied in 13,301 men and women from eastern Finland who were first interviewed in 1972 or 1977. For men, there was a graded association between extent of social connections and mortality. In multivariate models with adjustment for age, smoking, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
163
3
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(183 citation statements)
references
References 0 publications
11
163
3
6
Order By: Relevance
“…All of these variables are reported to have significant associations with mortality in various studies. [1][2][3][4][5]9 Availability of casual friends and support providers was derived from the following two questions: "Do you have a friend with whom you can talk frankly?" and "Do you have someone whom you can count on when you are in trouble?…”
Section: Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these variables are reported to have significant associations with mortality in various studies. [1][2][3][4][5]9 Availability of casual friends and support providers was derived from the following two questions: "Do you have a friend with whom you can talk frankly?" and "Do you have someone whom you can count on when you are in trouble?…”
Section: Measurementmentioning
confidence: 99%
“…[1][2][3][4][5] These studies have found that those with more social ties had a lower risk of mortality, independent of age and other physical or psychological factors.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[21][22][23] Recent evidence from the Nurses' Health Study, both cross-sectionally 24 and prospectively, 25 has demonstrated significant associations between social network characteristics (in particular, the absence of a close confidant), and reduction in physical functioning (after adjustment for health behaviours and comorbid conditions), equivalent in magnitude of effect 'to those observed among heavy smokers, or women in the highest category of body mass index (BMI) ( 24 , p. 711 our italics). Further work has noted that social relationships can be associated with mixed (both positive and negative) health effects according to their context and nature; for example, promoting self-esteem or dependence.…”
Section: Introductionmentioning
confidence: 99%
“…En las últimas décadas, diversos estudios epidemiológicos han puesto de manifiesto la asociación entre la falta de apoyo social y la mortalidad, en estudios de seguimiento en la población general [1][2][3][4][5] y en investigaciones centradas en la población anciana [6][7][8][9][10][11][12][13][14][15][16][17] . Sin embargo, la medida e incluso la definición del apoyo social ha sido abordada de formas muy distintas.…”
Section: Introductionunclassified